Combined use of 0.1% fluorometholone and meibomian gland expression improves symptoms of moderate and severe dry eye disease, even in patients with systemic immune disease. Issue 1 (1st January 2019) - Guo, Xuming; Li, Aipeng; Fan, Yi; Yu, Yanru; Guo, Wenhui; Jie, Ying
Abstract: This study prospectively evaluated the effect of 0.1% fluorometholone (FML) combined with meibomian gland expression (MGX) on dry eye disease (DED) and meibomian gland dysfunction (MGD).The study included 48 patients (96 eyes) with moderate to severe DED. The patients were treated with topical FML and MGX. The patients underwent Keratograph 5 M to evaluate quantitatively (THM, BUT, R-scan) and semi-quantitatively the meibomian gland loss (meiboscore). The methods included slit-lamp examination to evaluate meibum quality (meibum score), fluorescein staining and ocular surface disease index (OSDI) questionnaire. All patients (15 patients were also diagnosed with systemic immune disease) completed the study. The Schirmer I test results showed no statistical significance. After treatment, the fluorescein staining score, meibum score and R-Scan were decreased from the baseline values at week 2. The meiboscore was decreased at month 3 and the OSDI questionnaire scores were lower than the baseline at month 1. For subjects with systemic immune disease, the fluorescein staining score and meibum score were lower than the baseline. Tear BUT reached peak at month 1 and dropped to baseline at month 3. R-Scan and OSDI were decreased at months 1 and 3 compared to the baseline. The Schirmer I Test values and the meiboscore were not different from the baseline. The study demonstrated that 0.1% FML combined with MGX improves symptoms of moderate to severe DED.